Lower heart rate is associated with good one-year outcome in post-resuscitation patients. (July 2018) - Oksanen, Tuomas; Tiainen, Marjaana; Vaahersalo, Jukka; Bendel, Stepani; Varpula, Tero; Skrifvars, Markus; Pettilä, Ville; Wilkman, Erika; ,
Abstract: Background: Optimal hemodynamic goals in post-resuscitation patients are not clear. Previous studies have reported an association between lower heart rate and good outcome in patients receiving targeted temperature management (TTM) after out-of-hospital cardiac arrest. Methods: We analyzed heart rate (HR) and outcome data of 504 post-resuscitation patients from the prospectively collected database of the FINNRESUSCI study. One-year neurologic outcome was dichotomized by the Cerebral Performance Category (CPC) to good (1–2) or poor (3–5). Results: Of 504 patients, 40.1% (202/504) had good and 59.9% (302/ 504) had poor one-year neurologic outcome. Patients with good outcome had lower time-weighted mean HR during the first 48 h in the ICU (69.2 bpm [59.2–75.1] vs. 76.6 bpm [65.72–89.6], p < 0.001) and the first 72 h in the ICU (71.2 bpm [65.0–79.0] vs. 77.1 bpm [69.1–90.1, p < 0.001]). The percentage of HR registrations below HR threshold values (60, 80 and 100 bpm) were higher for patients with good neurologic outcome, p < 0.001 for all. Lower time-weighted HR for 0–48 h and 0–72 h, and a higher percentage of HR recordings below threshold values were independently associated with good neurological one-year outcome (p < 0.05 for all). When TTM and non-TTM patients were analyzed separately, HR parameters were independently associated with one-year neurologic outcome only in non-TTM patients. Conclusion: Lower heart rate was independently associated with good neurologic outcome. Whether HR in post-resuscitation patients is a prognostic indicator or an important variable to be targeted by treatment, needs to be assessed in future prospective controlled clinical trials.